Social aspects of science and technology in the investigative training of stomatology students - Edgar Bayés Cáceres; Rosario León Robaina; Aglae Cáceres Diéguez; Luisa Acosta Ortega (Medisan, 2019)
A literature and current documents review related to the pattern of the professional's training of stomatology career was carried out, in order to value the social aspects of science and technology that impact in the investigative training of the students of this career. It was observed little use of information and communications technologies to solve independent works, poor development of skills for internet searches and the implementation of this technologies in investigative activities for student teams, as well as limited integration of technologies in the curricular aspect. The necessity of an investigative training was reaffirmed in these students, taking into account the social, economic and technological complexity to integrate the new generations in the administration of knowledge and stimulate learning.